Biomanufacturing in Switzerland – Past, Present, and Future - Michael Altorfer; Jan M. Lucht; Hans-Peter Meyer (CHIMIA)
Chemistry and biotechnology played a central role in transforming a poverty-stricken region in the middle of Europe into a flourishing industrial country. Rural areas remained destitute well into the 18th century. However, during the second half of the 18th century the foundation of the chemical powerhouses was laid. The biotechnological sector was built on these strong fundaments. This paper describes the development of the Swiss biotechnology sector from the early beginnings in the 1930s with a biocatalytic step in Vitamin C production to today’s multifaceted application of biotechnology in Switzerland. As a matter of fact, biotechnology has become a key asset of the contemporary Swiss economy, and this paper outlines what is needed to stay on a successful path.